2020
DOI: 10.1126/sciadv.abc1693
|View full text |Cite
|
Sign up to set email alerts
|

Photopyroelectric microfluidics

Abstract: Precision manipulation of various liquids is essential in many fields. Unlike solid objects, fluids are intrinsically divisible, enriching their fundamental operations with merging, dispensing, and splitting on top of moving. Fluids are sticky as well, calling for their lossless manipulation to prevent mass loss and contamination. We present photopyroelectric microfluidics that meet all the requirements. In response to the irradiation from even one single beam of light, our platform creates a unique wavy diele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 44 publications
2
96
1
Order By: Relevance
“…For example, Lv and co-workers reported the propelling of fluid slugs in tubes functionalized with photo-responsive liquid crystal polymers, 35 and Li and co-workers generated droplet-propelling dielectrophoretic forces in a trilayer structure with a near-infrared laser beam. 36 However, the current setups include complex structured lenses, masks, and mirrors and often require a moving light source. [35][36][37][38][39] We have tried to tackle these challenges by generating continuous, mechanical surface waves by using azobenzene-modified liquid crystal coatings that are responsive to a uniform UV light source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Lv and co-workers reported the propelling of fluid slugs in tubes functionalized with photo-responsive liquid crystal polymers, 35 and Li and co-workers generated droplet-propelling dielectrophoretic forces in a trilayer structure with a near-infrared laser beam. 36 However, the current setups include complex structured lenses, masks, and mirrors and often require a moving light source. [35][36][37][38][39] We have tried to tackle these challenges by generating continuous, mechanical surface waves by using azobenzene-modified liquid crystal coatings that are responsive to a uniform UV light source.…”
Section: Introductionmentioning
confidence: 99%
“…36 However, the current setups include complex structured lenses, masks, and mirrors and often require a moving light source. [35][36][37][38][39] We have tried to tackle these challenges by generating continuous, mechanical surface waves by using azobenzene-modified liquid crystal coatings that are responsive to a uniform UV light source. 40 By tuning the molecular order and by controlling the polarization direction of the UV light, the trans-to-cis isomerization process is selectively activated, which induces a spatial distribution of macroscopic deformation.…”
Section: Introductionmentioning
confidence: 99%
“…Reported in Science Advances, a platform termed "photopyroelectric microfluidics" is developed to move, integrate and cut fluids using just a single beam of light in a lossfree manner [6]. By stacking three homogeneous layers -a photothermal film, a pyroelectric crystal, and a superomniphobic surface -the researchers demonstrate how a ray of light generates a wavy dielectrophoretic force profile through consecutive energy conversions.…”
Section: Liquid Processormentioning
confidence: 99%
“…The design of open surface microfluidics that enable orthogonal control of liquid mobility and chemical compositions is critical for devising the next generation of microfluidic platforms that will find use in applications across chemical (1)(2)(3)(4)(5), environmental (6,7), and biomedical fields (8)(9)(10). To achieve these desirable functionalities, extensive studies have demonstrated stimuli-responsive liquid mobility on open fluidic platforms based on either micro/nanoscale topographical surfaces (8,(11)(12)(13)(14)(15) or water-immiscible liquid-coated surfaces (16)(17)(18)(19). However, methods of manipulating droplets' chemical compositions tend to rely upon chemical adsorption directly from the underlying surface, which has been shown to subsequently pin droplets to the surface and render them immobile (7,20,21), as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%